2007
DOI: 10.1037/0022-006x.75.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Development of antisocial personality disorder in detained youths: The predictive value of mental disorders.

Abstract: Antisocial personality disorder (APD) is a serious public and mental health concern. Understanding how well conduct disorder (CD) and other mental disorders predict the development of APD among youth involved in the juvenile justice system is critical for prevention. This study used a stratified random sample of 1112 detained youth to examine the development of APD at a three-year followup interview. Nearly one fifth of male juvenile detainees later developed APD; approximately one quarter of male juvenile det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
5
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 63 publications
4
47
5
4
Order By: Relevance
“…Chez les enfants, des études ont montré que les troubles d'anxiété s'associent aux comportements agressifs (Washburn et al, 2007). Il est également démontré qu'il existe une comorbidité entre les troubles d'anxiété et les comportements perturbateurs (Dodge et al, 1997 ;Vitaro et al, 2002).…”
Section: R-deux De Nagelkerkeunclassified
“…Chez les enfants, des études ont montré que les troubles d'anxiété s'associent aux comportements agressifs (Washburn et al, 2007). Il est également démontré qu'il existe une comorbidité entre les troubles d'anxiété et les comportements perturbateurs (Dodge et al, 1997 ;Vitaro et al, 2002).…”
Section: R-deux De Nagelkerkeunclassified
“…This observation corresponds to studies of persistent violent offenders who demonstrate a stable pattern of antisocial behaviour since adulthood, and where a subgroup is characterized by the presence of co-morbid anxiety disorders and displays high levels of distress, neuroticism, disability and a poor quality of life (Sareen et al, 2004). Longitudinal studies have also shown that generalized anxiety disorder constitutes one risk factor for the development of antisocial personality disorder in adulthood (Washburn et al, 2007). Furthermore, in a national co-morbidity survey (Goodwin & Hamilton, 2003), more than half of those with diagnosis of antisocial personality disorder had a lifetime co-morbid anxiety disorder.…”
Section: Treatment Seekers: a Subcategory Of Antisocial Personality Dmentioning
confidence: 99%
“…In summary, if approximately 28% of those who enter the juvenile justice system have a prior formal diagnosis of ADHD, if the vast majority of 53% plus of juveniles in the system with CD would also be diagnosed with ADHD (if they were properly assessed), if the reported rates of 17.1% for males in the best study to date (Washburn et al, 2007) are an underestimate because of the inadequacies of assessment for ADHD, then a conservative prevalence estimate of 25% would seem to be reasonable.…”
Section: Prevalence Of Adhd In the Juvenile Criminal Justice Systemmentioning
confidence: 99%
“…In these studies, as previously discussed, the vast majority of those with CD were also diagnosed with ADHD. If this finding is applied to the 53% of males and females in detention or incarceration who have CD (Washburn et al, 2007) [note that 53% is an underestimate as it is based on self-report], then the vast majority of the 53% with CD would also presumably be diagnosed with ADHD if they were properly evaluated. Second, all studies that have assessed for ADHD in adolescents in all settings suffer from another limitation that results in an underestimation of true prevalence.…”
Section: Prevalence Of Adhd In the Juvenile Criminal Justice Systemmentioning
confidence: 99%
See 1 more Smart Citation